SPE Eastern Regional/Aapg Eastern Section Joint Meeting 2008
DOI: 10.2118/118175-ms
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Geochemical Scaling in Hydraulically Created Fractures: Laboratory and Field Studies

Abstract: Fracture conductivity values observed by well testing following hydraulic fracture stimulation treatments are often much lower than the values obtained by laboratory measurements for most proppants. In addition, many stimulated wells show loss of fracture conductivity with time, leading to reduced productivity and lost revenue.This rapid loss in fracture conductivity has been attributed to frac gel damage, embedment, proppant crushing, and fines invasion. All these damage mechanisms have been well studied in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that, by coating with a thin hydrophobic film, such as an ASMA, the treated surface is provided with the best protection against geochemical reactions that lead to loss of fracture conductivity caused by porosity-filling and compaction mechanisms (Weaver et al 2005Weaver and Nguyen 2010;Nguyen et al 2008). The use of ultralow-molecular-weight cationic OCS for formulating the ASMA solution also provides stabilization to the water-sensitive shale formations that operators often encounter in many unconventional reservoirs (Weaver et al 2011).…”
Section: Clay-control Agentmentioning
confidence: 99%
“…Previous studies have shown that, by coating with a thin hydrophobic film, such as an ASMA, the treated surface is provided with the best protection against geochemical reactions that lead to loss of fracture conductivity caused by porosity-filling and compaction mechanisms (Weaver et al 2005Weaver and Nguyen 2010;Nguyen et al 2008). The use of ultralow-molecular-weight cationic OCS for formulating the ASMA solution also provides stabilization to the water-sensitive shale formations that operators often encounter in many unconventional reservoirs (Weaver et al 2011).…”
Section: Clay-control Agentmentioning
confidence: 99%
“…Recent observations have demonstrated that hydrophobic coatings on proppant can extend their useful life by inhibiting diagenetic pressure dissolution and compaction reactions (Weaver et al 2005;Nguyen et al 2008) that result in the formation of porosity-filling mineral scales.…”
Section: Spe-174364-msmentioning
confidence: 99%
“…This mineral surface property change not only results in a stabilization of proppant and fines movement, but also results in a surface that is not conducive to the scale deposition. Recent observations have demonstrated that hydrophobic coatings on proppant can extend their useful life by inhibiting diagenetic pressure-solution and compaction reactions (Weaver et al 2005;Nguyen et al 2008) that result in the formation of porosity-filling mineral scales. The experiments performed in this study demonstrate how treating WBAA on sand or a proppant pack mitigate the formation of scale in the pack matrix.…”
Section: Introductionmentioning
confidence: 99%